Utilization of Paranet and Amount of Baglog Tearing Toward Enlargement of Cap and Total Fresh Weight of Oyster Mushroom (Pleurotus ostreatus) - Satyaningtyas, Marcelina Melvyn Gita; Herlina, Ninuk (Plantropica: Journal of Agricultural Science, 2024)
White oyster mushroom (Pleurotus ostreatus) is a type of popular mushroom in Indonesia. Some market demands require a wide cap size because it can add to the aesthetic value of the product and consumer satisfaction in consuming white oyster mushroom chips, especially the mushroom cap. This increased demand is not matched by high productivity so that farmers cannot meet market demand. This study aims to determine best treatment combination between amount of baglog tearing and paranet layer, to optimize oxygen levels by providing suitable humidity conditions for paranet layer, and to test the effectiveness of baglog tearing treatment, by giving paranet layer with proper tearing effectiveness is expected to increase the diameter of fruit cap and total fresh weight of mushrooms. This research was conducted at Kumbung Griya Jamur, Agriculture Faculty, Brawijaya University, Pucangsongo Village, Tumpang District, Malang Regency, East Java in January - April 2019. Method of this research used was a  Split Plot Design also the data were tested using ANOVA and 5% BNJ real test. The results of this study indicated that the best fruit cap diameter was produced in 2-layers paranet with the treatment of 1- layer tearing of 9.33 cm, which increased the fruit cap diameter by up to 86% compared to the 3-layer paranet treatment without tearing. The best total fresh weight was obtained from 2-layer paranet with a value of 877.2 g, which increased the total fresh weight by up to 19% when compared to the 1-layer paranet and 2-layer paranet treatment.